2012
DOI: 10.1007/s00125-012-2655-5
|View full text |Cite
|
Sign up to set email alerts
|

Common polymorphism near the MC4R gene is associated with type 2 diabetes: data from a meta-analysis of 123,373 individuals

Abstract: Aims/hypothesis Genome-wide association studies have shown that variants near the melanocortin 4 receptor gene (MC4R) (rs17782313 and rs12970134) are associated with risk of obesity in Europeans. As obesity is associated with an increased risk of type 2 diabetes, many studies have investigated the association between polymorphisms near the MC4R gene and type 2 diabetes risk across different ethnic populations, with inconsistent results. In this study, we performed a meta-analysis to clarify the association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
2
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 21 publications
5
42
2
4
Order By: Relevance
“…The MC4R gene encodes a downstream receptor in the leptin signaling pathway contributing to the central melanocortinergic system, which plays a vital role in metabolic regulation and energy intake [33] . The MC4R gene was one of the first and most widely studied loci from which genetic variations were associated with human obesity, and recent reports have shown associations between the rs17782313 SNP and obesity in GWAS as well as type 2 diabetes in a meta-analysis [34,35] . Contrary to the findings in our study, the MC4R-rs17782313 variant was not associated with HAZ after adjusting for age, gender, and BMIZ in children of a Chilean family cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The MC4R gene encodes a downstream receptor in the leptin signaling pathway contributing to the central melanocortinergic system, which plays a vital role in metabolic regulation and energy intake [33] . The MC4R gene was one of the first and most widely studied loci from which genetic variations were associated with human obesity, and recent reports have shown associations between the rs17782313 SNP and obesity in GWAS as well as type 2 diabetes in a meta-analysis [34,35] . Contrary to the findings in our study, the MC4R-rs17782313 variant was not associated with HAZ after adjusting for age, gender, and BMIZ in children of a Chilean family cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, the same variant near MC4R (rs17782313) showed evidence for association with LDL-C and TC in the Chinese Han population [49]. Another study indicated the significant association of rs17782313 polymorphism near the MC4R gene with type 2 diabetes risk, which was independent of BMI [50]. Several missense mutations in different transmembrane domains have been described.…”
Section: Discussionmentioning
confidence: 95%
“…Genome-wide association studies have shown that variants near the MC4R (rs17782313 and rs12970134) are associated with risk of obesity in Europeans. As obesity is associated with an increased risk of type 2 diabetes, many studies have investigated the association between polymorphisms near the MC4R gene and type 2 diabetes risk across different ethnic populations with inconsistent results [24]. To date, MC4R mutations have proven to be of large individual relevance but of small epidemiological relevance [18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, two recent meta-analyses indicated that the FTO and MC4R loci were associated with type 2 diabetes independently of BMI. 23,24 In addition, two other GWASs 8,9 have reported the associations between other identified BMI loci and risk of type 2 diabetes. However, for several other loci, the inclusive findings warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%